Solid electrolyte interface film, preparation method thereof, positive pole piece containing solid electrolyte interface film and lithium ion battery
By locally irradiating the electrode area of laser, the hydrolytic stability and high-temperature film formation problems of tri(trimethylsilane) phosphate in lithium-ion batteries are solved, and the efficient preparation of lithium-ion batteries is achieved, improving battery performance and process simplification.
Patent Information
- Application Number
- CN202411250984.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The application of tri(trimethylsilane) phosphate in lithium-ion batteries is limited by its poor hydrolysis stability and the need for strict anhydrous and anaerobic conditions, resulting in unsatisfactory film formation effect, complex process, and high-temperature film formation. The method will cause electrolyte decomposition and capacity decay.
By irradiating the electrode area locally by laser, local temperature concentration on the electrode surface is promoted, resulting in reaction of trimethylsilane phosphate with the electrolyte to form a solid electrolyte interface film, avoiding other areas of the electrolyte participating in film formation reaction and decomposition, simplifying the process and Improve reaction efficiency.
The excellent discharge capacity, Coulomb efficiency, cycling performance and AC impedance performance of lithium-ion batteries are achieved, while avoiding TMSP hydrolysis and electrolyte decomposition, simplifying the preparation process and improving film formation efficiency.
Smart Images

Figure CN119153773A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion batteries, and in particular relates to a solid electrolyte interface membrane and a preparation method thereof, a positive electrode sheet containing the solid electrolyte interface membrane, and a lithium ion battery. Background Art
[0002] Tris(trimethylsilyl)phosphate (TMSP) is a solid interfacial film-forming additive with broad application prospects in lithium-ion batteries. It has the advantage of forming films on both the positive and negative electrodes. In existing technical solutions, TMSP film formation depends on the chemical formation process. The film formation principle of TMSP mainly relies on direct electron transfer in the electrochemical process.
[0003] At the negative electrode, TMSP can silanize the electrolyte and improve the performance of the solid electrolyte interface film (SEI). The reaction equation of TMSP forming SEI film at the negative electrode is as follows:
[0004] [(CH3)9O4PSi3Li + ]+RO - →(CH3)6O3PSi2Li+ROSi(CH3)3(1)
[0005] Among them, R is determined by the electrolyte components and additive components, and ROSi(CH3)3 is the main organic component of TMSP as SEI film.
[0006] At the positive electrode, not only can the silicon atoms in TMSP act as electron acceptors to accept fluoride ions, but the phosphorus atoms can also act as electron donors to accept hydrogen protons. Both of these combinations can further react with the electrolyte to form a cathode electrolyte interface film (CEI). Thanks to the advantage of TMSP having dual active sites, its positive electrode film formation is very efficient; at the same time, it can also effectively remove HF in the electrolyte to prevent flatulence and corrosion. The reaction equation for TMSP to form a CEI film at the positive electrode is as follows:
[0007] (CH3)6O2PSi2F+C3H4O3→(CH3)6O2PSi2O(CH2)2O(CH2)2F+CO2(2)
[0008] (CH3)9O4PSi3+HF→(CH3)8O3PSi3F+CH3OH(3)
[0009] (CH3)6O3PSi2 . +C3H4O3→(CH3)6O3PSi2O(CH2)2OCOO . (4)
[0010] Among them, in formula (2) and formula (4), phosphorus is involved in the reaction as the active center, and in formula (3), silicon is involved in the reaction as the active center. The products formed themselves or in the form of dimers constitute the main components of the positive electrode CEI film.
[0011] However, the poor hydrolysis stability of TMSP limits its application. TMSP is extremely easy to hydrolyze to form trimethylsilanol and phosphoric acid, which leads to the failure of the additive, limiting its application in long-term storage and causing the film-forming effect to fail to meet expectations. The reaction equation between TMSP and trace water in the electrolyte is as follows:
[0012] (CH3)9O4PSi3+H2O→H3PO4+(CH3)3SiOH(5)
[0013] The existing process cannot completely remove the moisture introduced during the production process, which makes the TMSP film formation strictly dependent on the operation interval and storage time, which limits the process.
[0014] At present, the preparation of TMSP film often requires shortening the time interval between feeding and chemical formation, and the system must be strictly kept in an anhydrous and oxygen-free state. Although the literature and patents report the film formation method of TMSP in chemical formation, there is no relevant report on how to bypass the electrochemical process to directly regulate the film formation of TMSP.
[0015] In fact, TMSP can decompose between 120 and 250°C, and it can react with the electrolyte in the form of PO and Si-O bonds to form a solid electrolyte interface film. However, this technology is often not considered because such high temperatures will cause the electrolyte to decompose, ultimately causing serious capacity decay and destruction of active substances. The adverse effects of high temperature on the electrolyte far outweigh the positive effects of film formation.
[0016] Therefore, it is urgent to develop a method for forming a solid electrolyte interface membrane in which a lithium-ion battery has excellent battery discharge capacity, coulombic efficiency, cycle performance and AC impedance performance, while the preparation process can avoid most of the electrolyte from participating in the film formation reaction and decomposition, shorten the formation process time, improve the reaction efficiency, and avoid TMSP hydrolysis. Summary of the invention
[0017] The present invention provides a method for forming a solid electrolyte interface film, which achieves local temperature concentration on the electrode surface by laser local irradiation of the electrode area, so as to promote the decomposition of TMSP on the electrode surface and react with the electrolyte to form a solid electrolyte interface film, while other areas of the electrolyte remain at room temperature and do not participate in the film-forming reaction and decomposition. The method does not require a long chemical formation process, has a high reaction efficiency, avoids TMSP hydrolysis caused by long storage time, and the battery prepared by the method has a discharge capacity,
[0019] The coulombic efficiency, cycle performance and AC impedance performance are excellent.
[0020] Specifically, the present invention provides a method for preparing a solid electrolyte membrane, the method comprising the following steps:
[0021] (1) preparing an electrolyte solution containing tris(trimethylsilyl)phosphate;
[0022] (2) assembling a positive electrode sheet, a negative electrode sheet, a separator, and the electrolyte containing tris(trimethylsilyl)phosphate in step (1) to prepare a lithium-ion battery precursor;
[0023] (3) Using laser to irradiate the positive electrode plate area of the lithium ion battery precursor prepared in step (2) through the electrolyte, so that the solid electrolyte membrane is formed on the surface of the positive electrode plate, thereby obtaining a lithium ion battery intermediate.
[0024] In one or more embodiments, the electrolyte comprises an organic solvent, a lithium salt and an additive; in the electrolyte, the content of the organic solvent is 77wt% to 89wt%, the content of the lithium salt is 10wt% to 18wt%, the content of the additive is 1wt% to 5wt%, and the additive comprises tris(trimethylsilane) phosphate; preferably, the mass of tris(trimethylsilane) phosphate is 33wt% to 100wt% of the total mass of the additive.
[0025] In one or more embodiments, the organic solvent is ethylene carbonate and / or ethyl methyl carbonate.
[0026] In one or more embodiments, the additive further comprises vinylene carbonate.
[0027] In one or more embodiments, the lithium salt is LiPF6.
[0028] In one or more embodiments, the positive electrode plate comprises a current collector and a positive electrode material layer located on at least one surface of the current collector, the positive electrode material layer comprises a positive electrode active substance, a conductive agent and a binder; preferably, the conductive agent is conductive carbon black, the binder is polyvinylidene fluoride, and the positive electrode active substance is selected from one or more of lithium nickel cobalt manganese oxide, lithium iron manganese phosphate and LiCO2.
[0029] In one or more embodiments, the pulse power of the laser irradiation is 20 to 200 mJ / pulse / cm 2 , preferably 20 to 60 mJ / pulse / cm 2 .
[0030] In one or more embodiments, the pulse frequency of the laser irradiation is 8-12 Hz.
[0031] In one or more embodiments, the pulse width of the laser irradiation is 8-12 ns.
[0032] In one or more embodiments, the beam diameter of the laser irradiation is 8-12 mm.
[0034] In one or more embodiments, the wavelength of the laser irradiation is 1060-1070 nm.
[0035] In one or more embodiments, the laser irradiation time is 150-210 s.
[0036] In one or more embodiments, in step (3), after laser irradiation, the laser is removed and the lithium-ion battery precursor is left for a period of time, the leaving time being 25-35 minutes.
[0037] The invention provides a solid electrolyte interface membrane prepared by the method of the invention.
[0038] The present invention provides a positive electrode plate having the solid electrolyte interface film of the present invention on its surface.
[0039] The present invention provides a lithium-ion battery comprising the positive electrode plate of the present invention.
[0040] The present invention provides a method for preparing a lithium ion battery, the method comprising: forming a lithium ion battery intermediate prepared by the method of the present invention at 40-50°C to prepare the lithium ion battery; preferably, the formation time is 35-60 minutes.
[0041] The invention provides a lithium ion battery prepared by the method described in the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The schematic diagram is a schematic diagram of the decomposition of tris(trimethylsilyl)phosphate under high temperature of laser beam in some embodiments of the present invention.
[0043] Figure 2 Schematic diagram of the principle of film formation of tris(trimethylsilyl)phosphate by local heating under laser irradiation in some embodiments of the present invention. DETAILED DESCRIPTION
[0044] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0045] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0046] Herein, "comprising", "including", "containing" and similar terms cover the meanings of "consisting essentially of" and "consisting of", for example, when the present invention discloses "A comprises B and 241680
[0047] C", "A consists essentially of B and C" and "A consists of B and C" should be considered as disclosed herein.
[0048] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0049] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0050] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0051] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0052] The present invention provides a method for preparing a solid electrolyte membrane, the method comprising the following steps:
[0053] (1) preparing an electrolyte solution containing tris(trimethylsilyl)phosphate;
[0054] (2) assembling a positive electrode sheet, a negative electrode sheet, a separator, and the electrolyte containing tris(trimethylsilyl)phosphate in step (1) to prepare a lithium-ion battery precursor;
[0055] (3) Using laser to irradiate the positive electrode plate area of the lithium ion battery precursor prepared in step (2) through the electrolyte, so that a solid electrolyte film is formed on the surface of the positive electrode plate, thereby obtaining a lithium ion battery intermediate.
[0056] The method for preparing the solid electrolyte membrane of the present invention is as follows Figure 2 As shown, a lithium-ion battery precursor containing an electrolyte containing a TMSP film-forming additive is first assembled, and then a laser is used to irradiate the positive electrode plate area of the lithium-ion battery precursor through the electrolyte. The surface of the positive electrode plate is locally heated, and a solid electrolyte film is formed on the surface of the positive electrode plate after being left aside to cool.
[0057] In the present invention, tris(trimethylsilyl)phosphate in the electrolyte is decomposed under the high temperature of the laser beam, and the principle is as follows: Figure 1 shown.
[0059] In the present invention, the electrolyte contains an organic solvent, a lithium salt and an additive.
[0060] In the electrolyte of the present invention, the content of the organic solvent can be 77wt% to 89wt%, for example, 77wt%, 78wt%, 79wt%, 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, and 89wt%, calculated by mass percentage.
[0061] In the electrolyte of the present invention, the content of lithium salt can be 10wt% to 18wt% by mass, for example, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%.
[0062] In the electrolyte of the present invention, the content of the additive can be 1wt% to 5wt%, for example, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, calculated by mass percentage.
[0063] In the present invention, the mass of tris(trimethylsilyl)phosphate can be 33wt% to 100wt% of the total mass of the additive, for example 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 100wt%.
[0064] In the present invention, the organic solvent may be ethylene carbonate and / or ethyl methyl carbonate.
[0065] In the present invention, the additive can also include vinylene carbonate. In some embodiments, the total mass of vinylene carbonate and tris (trimethylsilane) phosphate is 1wt% to 5wt% of the mass of the electrolyte, such as 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%. In some embodiments, the mass of tris (trimethylsilane) phosphate is 33wt% to 100wt% of the total mass of vinylene carbonate and tris (trimethylsilane) phosphate, such as 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 100wt%. In some embodiments, the additive is composed of vinylene carbonate and tris (trimethylsilane) phosphate.
[0066] In the present invention, the lithium salt may be LiPF6.
[0067] In the present invention, the positive electrode sheet comprises a current collector and a positive electrode material layer located on at least one surface of the current collector, and the positive electrode material layer comprises a positive electrode active material, a conductive agent and a binder.
[0068] In the present invention, the conductive agent may be conductive carbon black.
[0069] In the present invention, the binder may be polyvinylidene fluoride.
[0070] In the present invention, the positive electrode active material can be selected from lithium nickel cobalt manganese oxide, lithium iron manganese phosphate and LiCO2
[0072] One or more of .
[0073] In the present invention, lithium nickel cobalt manganese oxide can be selected from LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.5 Co 0.2 Mn 0.3 One of O2 (NCM523).
[0074] In the present invention, the lithium iron manganese phosphate can be LiMn 0.7 Fe 0.3 PO4.
[0075] In the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on the surface of the negative electrode current collector. The negative electrode current collector may be a material commonly used in the art with excellent conductivity, such as copper foil. The negative electrode material layer includes a negative electrode active material, a conductive agent and a binder. The negative electrode material layer is obtained by coating a negative electrode slurry containing a negative electrode active material, a conductive agent, a binder and a solvent onto the negative electrode current collector, and then drying and pressing. The negative electrode active material, the conductive agent and the binder may be added to a solvent to prepare the negative electrode slurry. The solvent of the negative electrode slurry may be a conventional solvent in the art, such as deionized water. The negative electrode active material may be one or more selected from graphite (including artificial graphite, natural graphite), silicon-carbon negative electrode, hard carbon and lithium titanate, the conductive agent is preferably selected from one or more of conductive carbon black (such as acetylene black, Ketjen black), carbon fiber, graphene and carbon nanotubes, and the binder is preferably selected from one or more of fluorine-containing resin, polypropylene resin, fiber-type binder, rubber-type binder and polyimide-type binder. The negative electrode material layer and the negative electrode slurry may further include a thickener, such as sodium carboxymethylcellulose (CMC-Na).
[0076] The separator in the lithium ion battery of the present invention can be a polymer separator, a ceramic separator or a polymer / ceramic composite separator. The polymer separator includes a polyethylene (PE) separator, a polypropylene (PP) separator and a polyethylene terephthalate (PET) separator.
[0077] In the present invention, the positive electrode sheet and the negative electrode sheet are sequentially rolled, die-cut, dried, wound, assembled, placed in a PET separator, injected with an electrolyte, and sealed to obtain a lithium ion battery precursor.
[0078] In the present invention, the pulse power of laser irradiation can be 20 to 200 mJ / pulse / cm 2 , preferably 20 to 60 mJ / pulse / cm 2 . In the present invention, when the laser beam irradiation step is not used, because there is no local temperature rise, TMSP cannot reach the film-forming potential, and will not decompose to form a CEI film at this time. The lithium-ion battery prepared under the laser beam irradiation condition has a CEI film formed on the positive electrode, and the overall capacity, coulomb efficiency, and cycle life of the lithium-ion battery are improved. The film thickness of the CEI film is reduced compared to the film thickness of the conventional process, and the film formation impedance is reduced. However, if the laser pulse power is too high, the overall capacity, coulomb efficiency, and cycle life of the lithium-ion battery will decrease. This is because although the beam temperature rise does not diffuse into the electrolyte, it will diffuse into the electrode. The higher power causes the high temperature to destroy the internal structure of the electrode material, and ultimately the active material is affected, and the positive electrode plate cracks. Therefore, in the present invention, the pulse power of the laser irradiation is controlled within the above-mentioned preferred range, which is beneficial for the lithium-ion battery to maintain excellent overall capacity, coulomb efficiency, cycle life, AC impedance and electrode morphology.
[0079] In the present invention, the pulse frequency of laser irradiation can be 8-12 Hz, for example, 8 Hz, 9 Hz, 10 Hz, 11 Hz, 12 Hz.
[0080] In the present invention, the pulse width of laser irradiation can be 8-12ns, for example, 8ns, 9ns, 10ns, 11ns, 12ns.
[0081] In the present invention, the beam diameter of laser irradiation can be 8-12 mm, for example, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm.
[0082] In the present invention, the wavelength of laser irradiation can be 1060-1070nm, for example, 1060nm, 1062nm, 1064nm, 1068nm, 1070nm.
[0083] In the present invention, the laser irradiation time can be 150-210s, such as 150s, 160s, 170s, 180s, 190s, 200s, 210s. In the present invention, the longer the laser irradiation time, the more complete the film-forming reaction. If the laser irradiation time is too long, the temperature is too high, which will damage the electrode and the active material. Therefore, controlling the laser irradiation time within the above range is beneficial to taking into account the capacity and cycle life of the battery.
[0084] In step (3) of the present invention, after laser irradiation, the laser is removed and the lithium ion battery precursor is left for a period of time, and the leaving time can be 25-35 minutes, for example, 25 minutes, 27 minutes, 29 minutes, 30 minutes, 31 minutes, 33 minutes, 35 minutes.
[0085] The invention provides a solid electrolyte interface membrane prepared by the method of the invention.
[0086] The invention provides a positive electrode sheet having the solid electrolyte interface film of the invention on its surface.
[0087] The present invention provides a lithium ion battery comprising the positive electrode plate of the present invention. The lithium ion battery of the present invention has excellent overall capacity, coulomb efficiency, cycle life, AC impedance and electrode morphology.
[0088] The present invention provides a method for preparing a lithium ion battery, the method comprising: performing chemical reaction at 40-50° C. using a lithium ion battery intermediate prepared by the present invention to prepare a lithium ion battery; preferably, the chemical reaction time can be 35-60 min, for example, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min.
[0089] The present invention also provides a lithium ion battery prepared by the method of the present invention.
[0091] Compared with the prior art, the present invention has the following beneficial effects:
[0092] (1) In the present invention, the laser irradiated electrode area is locally overheated in situ to form a TMSP film;
[0093] (2) In the present invention, other components of the electrolyte do not participate in the film-forming reaction and remain stable;
[0094] (3) Compared with conventional chemical formation processes, the capacity retention rate and capacity recovery rate of the present invention are maintained or improved;
[0095] (4) Compared with conventional chemical formation processes, the AC impedance of the present invention is maintained or reduced;
[0096] (5) The reaction time of laser irradiation in the present invention is controlled within 5 minutes, which significantly improves the film forming efficiency and saves time cost compared with the chemical formation process of more than 5 hours.
[0097] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.
[0098] Example 1
[0099] (1) Preparation of electrolyte: In a glove box (water content <0.01 ppm, oxygen content <0.01 ppm), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were uniformly mixed in a mass ratio of 3:7, and a film-forming additive vinylene carbonate (VC) and a film-forming additive tris(trimethylsilyl) phosphate were added thereto, and the mixture was uniformly mixed to obtain a basic electrolyte, wherein the mass fraction of VC in the basic electrolyte was 2 wt %, and the mass fraction of TMSP was 1 wt %, and the basic electrolyte and LiPF6 were uniformly mixed in a mass ratio of 86:14 to obtain an electrolyte;
[0100] (2) Preparation of positive electrode sheet: 210 g of polyvinylidene fluoride (PVDF) powder was dissolved in 2791 g of N-methylpyrrolidone (NMP), and the PVDF glue solution with a solid content of 7 wt% was prepared after uniform stirring for use. 10 g of positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) and 0.3g conductive carbon black were mixed and stirred evenly, and the PVDF glue prepared above was added to the mixed dry materials, and after stirring evenly, the solid content of the slurry was adjusted to 60wt% with NMP, and then coated on a 9μm thick aluminum foil current collector to prepare a positive electrode sheet;
[0101] (3) Preparation of negative electrode sheet: 72 g of carboxymethyl cellulose (CMC) powder was dissolved in 3928 g of deionized water to prepare a CMC glue solution with a solid content of 1.8 wt % for use, 5 g of hard carbon and 0.17 g of conductive agent were mixed and stirred evenly, and then 6.3 g of the CMC glue solution prepared above and 0.51 g of styrene-butadiene rubber (SBR) were added to the mixed dry materials, stirred evenly, and then the solid content of the slurry was adjusted to 52.5 wt % with deionized water, and then coated on a 6 μm thick copper foil current collector to prepare a negative electrode sheet;
[0102] (4) Assembly of lithium-ion battery precursor: rolling, die-cutting, drying, winding, assembling, inserting PET separator, injecting prepared electrolyte, and sealing the positive electrode sheet and the negative electrode sheet to obtain a lithium-ion battery precursor;
[0103] (5) Laser film forming: 20mJ / pulse / cm 2 The laser beam was irradiated on the positive electrode plate through the electrolyte at a pulse frequency of 10 Hz, a pulse width of 10 ns, a beam diameter of 10 mm, and a wavelength of 1064 nm. After irradiation for 180 seconds, it was left for 30 minutes to obtain a lithium-ion battery intermediate, and the surface of the positive electrode plate had a solid electrolyte membrane;
[0104] (6) High temperature formation: At 45°C, the lithium-ion battery intermediate was placed for 20 min, charged to 3.45 V at a constant current of 0.02 C, placed for 5 min, then charged to 3.45 V at a constant current of 0.05 C, placed for 5 min, then charged to 3.65 V at a constant current of 0.1 C, placed for 5 min, and then charged to 3.65 V at a constant current of 0.2 C to obtain a lithium-ion battery.
[0105] Example 2
[0106] The other conditions were the same as those in Example 1, except that the laser pulse power was increased from 20 mJ / pulse / cm 2 Replaced with 40mJ / pulse / cm 2 .
[0107] Example 3
[0108] The other conditions were the same as those in Example 1, except that the laser pulse power was increased from 20 mJ / pulse / cm 2 Replaced with 100mJ / pulse / cm 2 .
[0109] Example 4
[0110] The other conditions were the same as those in Example 1, except that the laser pulse power was increased from 20 mJ / pulse / cm 2 Replaced with 200mJ / pulse / cm2 .
[0112] Example 5
[0113] The other conditions were the same as those in Example 1, except that the positive electrode active material in the process of preparing the positive electrode sheet was replaced by LiCO2 from NCM811 and the laser pulse power was increased from 20 mJ / pulse / cm 2 Replaced with 40mJ / pulse / cm 2 .
[0114] Example 6
[0115] The other conditions were the same as those in Example 1, except that the positive electrode active material in the process of preparing the positive electrode sheet was replaced by LiNi instead of NCM811. 0.5 Co 0.2 Mn 0.3 O2 (NCM523), laser pulse power from 20mJ / pulse / cm 2 Replaced with 40mJ / pulse / cm 2 .
[0116] Example 7
[0117] The other conditions were the same as those in Example 1, except that the positive electrode active material in the process of preparing the positive electrode sheet was replaced by LiMn from NCM811. 0.7 Fe 0.3 PO4, laser pulse power from 20mJ / pulse / cm 2 Replaced with 40mJ / pulse / cm 2 .
[0118] Example 8
[0119] The other conditions were the same as those in Example 1, except that the laser pulse power was increased from 20 mJ / pulse / cm 2 Replaced with 60mJ / pulse / cm 2 .
[0120] Comparative Example 1
[0121] The other conditions are the same as those in Example 1, except that step (5) is not included, that is, the lithium ion battery precursor prepared in step (4) is directly subjected to the high temperature formation process in step (6).
[0122] Comparative Example 2
[0123] (1) Preparation of precursor solution: 1 wt % of tris(trimethylsilyl) phosphate, 2 wt % of vinylene carbonate, 29.1 wt % of ethylene carbonate, and 67.9 wt % of ethyl methyl carbonate were mixed to prepare a precursor solution;
[0124] (2) Preparation of positive electrode sheet: 210 g of polyvinylidene fluoride (PVDF) powder was dissolved in 2791 g of N-methylpyrrolidone (NMP), and stirred evenly to obtain 241680 with a solid content of 7 wt%.
[0125] PVDF glue solution is ready for use. 10 kg of positive electrode active material (LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) and 0.3kg conductive carbon black were mixed and stirred evenly, and the PVDF glue prepared above was added to the mixed dry materials, and after stirring evenly, the solid content of the slurry was adjusted to 60wt% with NMP, and then coated on a 9μm thick aluminum foil current collector to prepare a positive electrode sheet;
[0126] (3) Laser film forming: 40mJ / pulse / cm 2 The laser beam was irradiated through the electrolyte at a pulse frequency of 10 Hz, a pulse width of 10 ns, a beam diameter of 10 mm, and a wavelength of 1064 nm onto the positive electrode sheet immersed in the precursor solution. After irradiation for 180 seconds, the positive electrode sheet was left for 30 minutes to obtain a positive electrode sheet with a solid electrolyte film on the surface.
[0127] (4) Preparation of electrolyte: In a glove box (water content <0.01ppm, oxygen content <0.01ppm), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were uniformly mixed in a mass ratio of 3:7, and film-forming additives vinylene carbonate (VC) and tris(trimethylsilyl) phosphate were added thereto, and the mixture was uniformly mixed to obtain a basic electrolyte, wherein the mass fraction of VC in the basic electrolyte was 2wt%, and the mass fraction of TMSP was 1wt%. The basic electrolyte and LiPF6 were uniformly mixed in a mass ratio of 86:14 to obtain an electrolyte;
[0128] (5) Preparation of negative electrode sheet: 72 g of carboxymethyl cellulose (CMC) powder was dissolved in 3928 g of deionized water to prepare a CMC glue solution with a solid content of 1.8 wt % for use, 5 g of hard carbon and 0.17 g of conductive agent were mixed and stirred evenly, and then 6.3 g of the CMC glue solution prepared above and 0.51 g of styrene-butadiene rubber (SBR) were added to the mixed dry materials, stirred evenly, and then the solid content of the slurry was adjusted to 52.5 wt % with deionized water, and then coated on a 6 μm thick copper foil current collector to prepare a negative electrode sheet;
[0129] (6) Assembly of lithium-ion battery intermediates: rolling, die-cutting, drying, winding, assembling, inserting PET separators, injecting prepared electrolytes, and sealing the positive electrode sheets and negative electrode sheets in sequence to obtain lithium-ion battery intermediates;
[0130] (7) High temperature formation: At 45°C, the lithium-ion battery intermediate was placed for 20 min, charged to 3.45 V at a constant current of 0.02C, placed for 5 min, then charged to 3.45 V at a constant current of 0.05C, placed for 5 min, then charged to 3.65 V at a constant current of 0.1C, placed for 5 min, and then charged to 3.65 V at a constant current of 0.2C to obtain a lithium-ion battery.
[0131] Test Case
[0132] Cycle test: Place the battery at 25°C for 30 minutes, charge to 3.65V at a constant power of 1P, then place it for 5 minutes, discharge to 2.00V at a constant power of 1P, then place it for 5 minutes. Repeat the above steps 50, 100, and 500 times, and collect the discharge capacity data after 50 times, the coulomb efficiency data after 100 times, and the cycle capacity retention rate data after 500 weeks.
[0133] 100% SOC AC impedance test: The lithium-ion battery is placed at 25°C for 30 minutes, and its AC impedance data is obtained after it is charged to 100% SOC.
[0134] CEI film average thickness and electrode morphology test: The electrode morphology was observed using a transmission scanning electron microscope, the average thickness of the CEI film within 500 nm was calculated, and then the cracking condition was characterized by related morphology.
[0135] The discharge capacity after 50 cycles, the coulombic efficiency after 100 cycles, the capacity retention rate after 500 cycles, the 100% SOC AC impedance, the average thickness of the CEI film, and the electrode morphology of Examples 1-8 and Comparative Examples 1-2 were tested. The results are shown in Table 1.
[0136] Table 1: Discharge capacity, coulombic efficiency, cycle performance, AC impedance, average CEI film thickness and electrode morphology of the lithium ion batteries of Examples 1-8 and Comparative Examples 1-2
[0137]
[0138] From the comparison between Comparative Example 1 of the present application and Examples 1, 2, 3, 4, 5, 6 and 7, it can be seen that when the laser beam irradiation step is not used, due to the lack of local temperature rise, TMSP cannot reach the film-forming potential and will not decompose to form a CEI film, resulting in a sharp drop in the cycle capacity retention rate. On this basis, the effectiveness of the laser irradiation film-forming method is verified.
[0139] From the comparison between Example 1 and Comparative Example 1 in Table 1, it can be seen that compared with the lithium ion battery prepared without the laser film forming operation step in Comparative Example 1, the laser pulse power of Example 1 is 20mJ / pulse / cm 2 The lithium-ion battery prepared under laser beam irradiation conditions has a CEI film formed on the positive electrode, which improves the overall capacity and coulomb efficiency of the battery, and the better film formation stability improves the cycle life; in addition, the film thickness of the CEI film is thinner than that of the conventional process, which makes it have a lower film formation impedance.
[0140] In Example 1, when the laser pulse power is 20 mJ / pulse / cm 2 The lithium-ion battery prepared under the conditions of laser beam irradiation of 20 mJ / pulse / cm 2 The data comparison of the lithium-ion batteries prepared under the laser beam irradiation conditions in Table 1 shows that the laser pulse power is increased from 20mJ / pulse / cm 2 Increased to 40mJ / pulse / cm 2 It is beneficial to improve the overall capacity, coulombic efficiency and cycle life of the battery. This is because the temperature increase brought about by higher power is more significant, and the film-forming reaction of TMSP and electrolyte is more complete; in addition, the film thickness is further reduced accordingly, reducing the film-forming impedance.
[0141] In Example 2, when the laser pulse power is 40 mJ / pulse / cm 2 The lithium ion battery prepared under the conditions of laser beam irradiation of 100 mJ / pulse / cm 2 The data comparison of the lithium-ion battery prepared under the laser beam irradiation conditions in Table 1 shows that the laser pulse power is increased from 40mJ / pulse / cm 2 Increased to 100mJ / pulse / cm 2 This is not conducive to the overall capacity, coulombic efficiency and cycle life of the battery. This is because although the cluster temperature rise does not diffuse into the electrolyte, it will diffuse into the electrode. Higher power will cause high temperature to destroy the internal structure of the electrode material, and ultimately affect the active material, reflecting a decline in performance. The cracking phenomenon of the positive electrode under microscopy further verifies this conclusion.
[0142] In Example 3, when the laser pulse power is 100 mJ / pulse / cm 2 The lithium-ion battery prepared under the conditions of laser beam irradiation of 200 mJ / pulse / cm 2The data comparison of the lithium-ion batteries prepared under the laser beam irradiation conditions in Table 1 shows that the laser pulse power is increased from 100mJ / pulse / cm 2 Increased to 200mJ / pulse / cm 2 This is not conducive to the overall capacity, coulombic efficiency and cycle life of the battery. This is because although the cluster temperature rise does not diffuse into the electrolyte, it will diffuse into the electrode. Higher power will cause high temperature to destroy the internal structure of the electrode material, and ultimately affect the active material, reflecting the decline in performance. The positive electrode has many obvious cracks under the microscope.
[0143] Based on the battery performance in Example 1, Example 2, Example 3 and Example 4, it is concluded that the optimal laser power should be controlled at 40mJ / pulse / cm 2 about.
[0144] From the data comparison in Table 1 of the lithium ion battery in Example 5 in which the positive electrode active material is LiCO2 and the lithium ion battery in Example 2 in which the positive electrode active material is NCM811, it can be seen that the technology of local heating of the laser beam and decomposition of TMSP to form a CEI film at the positive electrode can also be applied to traditional LiCO2 materials, and maintains good capacity, coulomb efficiency and cycle life, and the formed solid electrolyte interface film can be observed under a microscope.
[0145] From the data comparison of the lithium ion battery in Example 6 in which the positive electrode active material is NCM811 and the lithium ion battery in Example 2 in which the positive electrode active material is NCM811 in Table 1, it can be seen that the technology of local heating of the laser beam and decomposition of TMSP for forming a CEI film at the positive electrode can also be applied to other NCM materials with different element contents, and have similar capacity, coulomb efficiency and cycle life (slightly lower than NCM811), and the formed solid electrolyte interface film can be observed under a microscope.
[0146] From the data comparison of the lithium-ion battery in Example 6 with the positive electrode active material NCM811 and the lithium-ion battery in Example 2 with the positive electrode active material NCM811 in Table 1, it can be seen that the technology of laser beam local heating and decomposition of TMSP for forming CEI film on the positive electrode can be extended to iron manganese lithium phosphate materials, and maintain good capacity, coulomb efficiency and cycle life.
[0147] The solid electrolyte interface film was observed.
[0148] Based on Example 5, Example 6, and Example 7, the applicability of the laser decomposition TMSP film-forming technology is verified, and it can be further extended to positive electrode active materials in different application fields.
[0149] From the data comparison in Table 1 of the positive electrode film-forming method of in-situ laser irradiation in an electrolyte environment in Example 2 and the method of first immersing the positive electrode plate in a precursor solution for local laser irradiation film-forming, and then preparing the battery in Comparative Example 2, it can be seen that the positive electrode film-forming method of in-situ laser irradiation in an electrolyte environment is better than the positive electrode first immersed in a precursor solution for local laser irradiation film-forming, and then subsequently preparing the battery, for improving the battery cycle performance and coulomb efficiency. This is mainly because the process of in-situ film formation in the electrolyte is accompanied by changes in the electrolyte components. After the positive electrode is first locally laser irradiated to form a film, the components of the injected liquid are different from those after the precursor solution is consumed, which affects the compatibility of the film formation in the subsequent formation process. Based on this experimental phenomenon, it is proved that after the battery is made, the method of in-situ laser irradiation of the positive electrode is more effective in improving the battery cycle performance than the method of first forming a positive electrode film in a precursor solution and then making the battery.
Claims
1. A method for preparing a solid electrolyte membrane, characterized in that: The method comprises the following steps: (1) preparing an electrolyte solution containing tris(trimethylsilyl)phosphate; (2) assembling a positive electrode sheet, a negative electrode sheet, a separator, and the electrolyte containing tris(trimethylsilyl)phosphate in step (1) to prepare a lithium-ion battery precursor; (3) Using laser to irradiate the positive electrode plate area of the lithium ion battery precursor prepared in step (2) through the electrolyte, so that the solid electrolyte membrane is formed on the surface of the positive electrode plate, thereby obtaining a lithium ion battery intermediate.
2. The method according to claim 1, characterized in that The electrolyte comprises an organic solvent, a lithium salt and an additive; in the electrolyte, by weight percentage, the content of the organic solvent is 77wt% to 89wt%, the content of the lithium salt is 10wt% to 18wt%, the content of the additive is 1wt% to 5wt%, and the additive comprises tris(trimethylsilyl)phosphate; preferably, the mass of tris(trimethylsilyl)phosphate is 33wt% to 100wt% of the total mass of the additive.
3. The method according to claim 2, characterized in that The method has one or more of the following features: The organic solvent is ethylene carbonate and / or ethyl methyl carbonate; The additive also includes vinylene carbonate; The lithium salt is LiPF6.
4. The method according to claim 1, characterized in that The positive electrode plate comprises a current collector and a positive electrode material layer located on at least one surface of the current collector, the positive electrode material layer comprises a positive electrode active substance, a conductive agent and a binder; preferably, the conductive agent is conductive carbon black, the binder is polyvinylidene fluoride, and the positive electrode active substance is selected from one or more of lithium nickel cobalt manganese oxide, lithium iron manganese phosphate and LiCO2.
5. The method according to claim 1, characterized in that The method has one or more of the following features: The pulse power of the laser irradiation is 20-200 mJ / pulse / cm 2 , preferably 241680 20~60mJ / pulse / cm 2 ; The pulse frequency of the laser irradiation is 8-12 Hz; The pulse width of the laser irradiation is 8-12ns; The beam diameter of the laser irradiation is 8-12 mm; The wavelength of the laser irradiation is 1060-1070nm. The laser irradiation time is 150-210s. In step (3), after laser irradiation, the laser is removed and the lithium-ion battery precursor is left for a period of time, the leaving time being 25-35 minutes.
6. A solid electrolyte interface membrane prepared by the method according to any one of claims 1 to 5.
7. A positive electrode sheet, characterized in that: The surface of the positive electrode sheet has the solid electrolyte interface film according to claim 6.
8. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet according to claim 7.
9. A method for preparing a lithium ion battery, characterized in that: The method comprises: forming a lithium ion battery intermediate obtained by the method according to any one of claims 1 to 5 at 40 to 50° C. to obtain the lithium ion battery; preferably, the formation time is 35 to 60 minutes.
10. A lithium ion battery prepared by the method according to claim 9.
Citation Information
Patent Citations
Flexible solid-state battery containing electron conduction interface layer and preparation method thereof
CN111799466A
Laser-assisted positive electrode interface layer construction method
CN113937252A
Laser-assisted high-ionic-conductivity solid-state battery and preparation method thereof
CN118054069A
Nonaqueous electrolytic liquid and lithium secondary battery employing same
CN1411619A
Non-aqueous liquid electrolyte and lithium secondary battery comprising the same
KR1020160036807A
